KETERLIBATAN IKPMD INDONESIA- YOGYAKARTA PADA KEBIJAKAN PEMERINTAH DAERAH KOTA YOGYAKARTA DALAM MEWUJUDKAN SPIRIT MULTIKULTURALISME - Andi Nur Fiqhi Uramai; Asriani Asriani; Zainuddin Losi (Jurnal Arajang, 2019)
Indonesia as a multicultural country, has a diversity consisting cultural, ethnic and language. To observe, Yogyakarta is the one of Indonesian province displayed that diversity. Thus Yogyakarta often called as ‘Indonesian miniature’, while the diversity can lead to horizontal conflicts in Yogyakarta. IKPMDI-Y established as a communicative forum to reduce horizontal conflicts. Therefore, in this research, the author observe the role of IKPMDI-Y involved in Yogyakarta Government Policies for building spirit of multiculturalism.The author uses quantitative method case study which use descriptive approach and theory as a research tool. While unit analize is IKPMDI-Y organization, and the research scope in Yogyakarta city.The researcher found the IKPMDI-Y involved in Yogyakarta Government Policie which delivering the spirit of multiculturalism. Where IKPMDI-Y is forum which unify the students/ regional organization from various ethnic groups and languages in Yogyakarta. Therfore IKPMDI-Y leads the active role in realizing the spirit of multiculturalism in Yogyakarta city.